Sony Corporation / Nahamizun Maamor - Maamor, Nahamizun (2022)
This project aims to determine how ideas can be implemented in a realistic environment. Every student at UiTM Arau is required to complete a case study project as part of their studies. I have selected Sony Corporation for my research company and Sony Xperia 5 Mark II which is the product from their company as the main target for my analysis. In the first part of the project report, I able to collect general information about the company such as the background of the company, technology used, and different kinds of electronic products that the company manufactured. In the second part of the project study, by conducting a SWOT analysis for the product, I was able to identify the product's strengths, weaknesses, opportunities, and threats, as well as determine a better technology framework solution to address product issues as give recommendation and improvement for the new product our company.